Thermal and radiation shielding characteristics of erbium ions doped zinc tellurite glasses - Mohd Haniff Mohd Tahir (Tanjung Malim, 2024)
Thermal and radiation shielding characteristics of erbium ions doped zinc tellurite glasses by Mohd Haniff Mohd Tahir